Penerapan Pembelajaran Pendidikan Agama Kristen Adaptif dalam Menghadapi Tantangan Teknologi Pendidikan - Udin Firman Hidayat; Martha Megawati Pasaribu; Djoys Anneke Rantung; Noh Ibrahim Boiliu (Journal on Education, 2023)
Educational goals are important things that are pursued through the curriculum and the entire learning process in the classroom. Educators have a responsibility to be able to overcome every problem and challenges faced in the learning process. No exception in learning Christian Religious Education (PAK), educators must be able to develop learning that is relevant in overcoming the challenges. This research is an attempt to apply adaptive PAK learning as a solution to face the challenges of educational technology. Using descriptive qualitative research methods and a literature study approach, this research shows that adaptive PAK learning is implemented by developing alternative learning models, maximizing the functions and roles of KKG and MGMP, and strengthening collaboration between schools, churches, and families in organizing PAK